Home-Based Entrepreneurship Training for Enhancing Family Income in Takalar Regency - Nurhayani Nurhayani; Hasisa Haruna; Andi Anggi Kemalasari; Nur Rahmi; Sumiati Tahir (Politeknik Pariwisata Makassar, 2026)
This community service program aims to enhance the economic capacity and independence of the community through home-based entrepreneurship training in Takalar Regency. The primary challenges faced by the community include limited skills in developing home-based businesses, a lack of product innovation, and insufficient knowledge of marketing and business management. Therefore, this program was implemented as a community empowerment initiative, particularly targeting housewives and small-scale entrepreneurs, to enable them to transform local resources into products with economic value. The implementation method consisted of several stages, including observation, socialization, training, hands-on practice, and business mentoring. The training materials covered the fundamentals of entrepreneurship, home-based product processing, packaging techniques, basic digital marketing, and financial management for small businesses. The program was conducted using a participatory approach that actively involved community members in both the training sessions and production practices. The results demonstrated a significant improvement in participants’ knowledge and skills in managing home-based businesses. Participants were able to produce more attractive products with higher market value than before. In addition, they gained a better understanding of the importance of marketing strategies through social media to expand their consumer reach. The program also positively influenced participants’ motivation to develop independent businesses as a means of increasing family income. In conclusion, home-based entrepreneurship training has proven effective in supporting community economic empowerment in Takalar Regency. This initiative is expected to serve as an initial step toward creating productive and sustainable enterprises based on local potential.